2020
DOI: 10.2105/ajph.2019.305460
|View full text |Cite
|
Sign up to set email alerts
|

Negative Police Encounters and Police Avoidance as Pathways to Depressive Symptoms Among US Black Men, 2015–2016

Abstract: Objectives. To examine negative police encounters and police avoidance as mediators of incarceration history and depressive symptoms among US Black men and to assess the role of unemployment as a moderator of these associations. Methods. Data were derived from the quantitative phase of Menhood, a 2015–2016 study based in Washington, DC. Participants were 891 Black men, 18 to 44 years of age, who completed computer surveys. We used moderated mediation to test the study’s conceptual model. Results. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 23 publications
3
64
0
Order By: Relevance
“…Overall, recent work reveals that perceived respect may function as a mediator between police encounters and mental health symptoms. Although no known work has investigated this relationship directly, one study demonstrated that the relationship between incarceration history and depression symptoms was mediated by negative police encounters and police avoidance (Bowleg et al, 2020). Although police avoidance is distinct from perceived fairness, this study provides evidence that attitudes towards police may act as a mediator between police contact and psychological symptomology.…”
mentioning
confidence: 58%
“…Overall, recent work reveals that perceived respect may function as a mediator between police encounters and mental health symptoms. Although no known work has investigated this relationship directly, one study demonstrated that the relationship between incarceration history and depression symptoms was mediated by negative police encounters and police avoidance (Bowleg et al, 2020). Although police avoidance is distinct from perceived fairness, this study provides evidence that attitudes towards police may act as a mediator between police contact and psychological symptomology.…”
mentioning
confidence: 58%
“…Although the negative health/public health consequences of police arrests and incarceration has been documented ( Bowleg et al, 2020 ), there is paucity of research on the interplay of police arrest and suicide ideation. This study examined police arrest, (both lifetime for any reason and marijuana related arrest), and suicide ideation among young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Following the data, we developed quantitative measures to assess these experiences with the study’s larger sample. Advocating for SBS researchers to critically engage with the topic of anti-Black racist police is now central to my team’s health equity research (e.g., Bowleg, del Río González, et al, 2020; Bowleg et al, 2021; Bowleg, Teti, et al, 2020).…”
Section: Embrace a Critical Qualitative Stancementioning
confidence: 99%